A molecular comparative study of intestinal colonization with Staphylococcus aureus between pediatric inpatients and outpatients of different age groups - Shaoxiang Lin; Zhile Xiong; Chao Zhang; Shuyan Liu; Tongyan Ding; Kaiyue Yang; Yunxing He; Zhimin Zhao; Zhenwen Zhou (Microbiology Spectrum)
ABSTRACT Currently, Staphylococcus aureus (S. aureus) is one of the leading causes of death from infectious diseases worldwide. Our aim in this study was to investigate and compare the molecular epidemiology and antibiotic resistance of S. aureus colonizing the intestinal tract of pediatric inpatients and outpatients of different age groups. We analyzed stool samples from 1,300 patients at a children’s hospital in Shenzhen, China. After culturing S. aureus, we used matrix-assisted laser desorption/ionization time-of-flight mass spectrometry to identify the strains. In addition, we performed antimicrobial susceptibility testing on isolated S. aureus strains as well as pheno- and genotypic characterization by PCR. S. aureus was detected in 104 out of 1,300 (8.0%) patients, including 20 out of 1,300 (1.5%) patients with methicillin-resistant S. aureus (MRSA). MRSA accounted for 19.2% of the S. aureus isolates. The resistance rates of S. aureus strains to penicillin, erythromycin, clindamycin, levofloxacin, and moxifloxacin were 83.7%, 34.6%, 31.7%, 3.9%, and 3.9%, respectively. None of the strains showed resistance to linezolid, daptomycin, tigecycline, vancomycin, or tetracycline. One hundred fou strains of S. aureus revealed that 49.0% (51/104) harbored enterotoxin genes, and most enterotoxin-positive strains carried only one gene type (90.2%, 46/51), while a minority carried two gene types (9.8%, 5/51). Besides, a total of 29 sequence types (STs) were identified with the three most prevalent STs: ST45, ST188, and ST6, accounting for 12.5%, 12.5%, and 9.6%. We found that the molecular characteristics of S. aureus in intestinal colonization of children have regional differences. To provide a theoretical basis for the prevention and control of S. aureus infections, increased surveillance of local S. aureus resistance and molecular epidemiological characteristics is needed.IMPORTANCEThis study assessed the clinical and molecular epidemiology of Staphylococcus aureus in pediatric patients at a children’s hospital in Shenzhen, South China by means of screening stool samples for pheno- and genotypic characterization for carriage of S. aureus. Of 1,300 fecal samples screened, 104 (8.0%) were positive for S. aureus with 19.2% methicillin-resistant S. aureus. The resistance rates of S. aureus to penicillin, erythromycin, clindamycin, levofloxacin, and moxifloxacin were 83.7%, 34.6%, 31.7%, 3.9%, and 3.9%, respectively. None of the strains showed resistance to linezolid, daptomycin, tigecycline, vancomycin, or tetracycline. One hundred four strains of S. aureus revealed that 49.0% (51/104) harbored enterotoxin genes, and most enterotoxin-positive strains carried only one gene type (90.2%, 46/51), while a minority carried two gene types (9.8%, 5/51). Besides, a total of 29 sequence types (STs) were identified with the three most prevalent STs: ST45, ST188, and ST6, accounting for 12.5%, 12.5%, and 9.6%.